Nonoperative management for patients with grade IV blunt hepatic trauma - Zago, Thiago Messias (BioMed Central, 2012)
INTRODUCTION: The treatment of complex liver injuries remains a challenge. Nonoperative treatment for such injuries is increasingly being adopted as the initial management strategy. We reviewed our experience, at a University teaching hospital, in the nonoperative management of grade IV liver injuries with the intent to evaluate failure rates; need for angioembolization and blood transfusions; and in-hospital mortality and complications. METHODS: This is a retrospective analysis conducted at a single large trauma centre in Brazil. All consecutive, hemodynamically stable, blunt trauma patients with grade IV hepatic injury, between 1996 and 2011, were analyzed. Demographics and baseline characteristics were recorded. Failure of nonoperative management was defined by the need for surgical intervention. Need for angioembolization and transfusions, in-hospital death, and complications were also assessed RESULTS: Eighteen patients with grade IV hepatic injury treated nonoperatively during the study period were included. The nonoperative treatment failed in only one patient (5.5%) who had refractory abdominal pain. However, no missed injuries and/or worsening of bleeding were observed during the operation. None of the patients died nor need angioembolization. No complications directly related to the liver were observed. Unrelated complications to the liver occurred in three patients (16.7%); one patient developed a tracheal stenosis (secondary to tracheal intubation); one had pleural effusion; and one developed an abscess in the pleural cavity. The hospital length of stay was on average 11.56 days. CONCLUSIONS: In our experience, nonoperative management of grade IV liver injury for stable blunt trauma patients is associated with high success rates without significant complications.